Three new players in energy regulation: Preptin, adropin and irisin - Aydin, Suleyman (Elsevier Science Inc, 2014)
Homeostasis of energy is regulated by genetic factors, food intake, and energy expenditure. When energy input is greater than expenditure, the balance is positive, which can lead to weight gain and obesity. When the balance is negative, weight is lost. Regulation of this homeostasis is multi-factorial, involving many orexigenic (appetite-stimulating) and anorexigenic (appetite-suppressing) peptide hormones. Peripheral tissues are now known to be involved in weight regulation and research on its endocrine characteristics proceeds apace. Preptin with 34 amino acids (MW 3948 Da), adropin with 43 amino acids and a molecular weight of (4999 Da), and irisin with 112 amino acids (12587 Da), are three newly discovered peptides critical for regulating energy metabolism. Preptin is synthesized primarily in pancreatic beta cells, and adropin mainly in the liver and brain, and many peripheral tissues. Irisin, however, is synthesized principally in the heart muscle, along with peripheral tissues, including salivary glands, kidney and liver. The prime functions of preptin and adropin include regulating carbohydrate, lipid and protein metabolisms by moderating glucose-mediated insulin release. Irisin is an anti-obesitic and anti-diabetic hormone regulating adipose tissue metabolism and glucose homeostasis by converting white to brown adipose tissue. This review offers a historical account of these discovery and function of these peptides, including their structure, and physiological and biochemical properties. Their roles in energy regulation will be discussed. Their measurement in biological fluids will be considered, which will lead to further discussion of their possible clinical value. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Preptin; Adropin; Irisin; Energy regulation